Biology of the black clam, Villorita cyprinoides (Gray) in the backwaters of Vembanad Lake - Laxmilatha, P; Velayudhan, T S (Indian Journal of Fisheries, 2011)
Biology of the black clam from two fishing sites of the Vembanad Lake was studied. The environmental conditions of the two sites were also monitored. The observed differences in the growth pattern and breeding biology of the black clam from Nettoor and Muhamma are correlated to the hydrological parameters. These characteristics are discussed.